An Interplay Between Post-Traumatic Epilepsy and Associated Cognitive Decline: A Systematic Review - Ngadimon, Irma Wati; Aledo-Serrano, Angel; Arulsamy, Alina; Mohan, Devi; Khoo, Ching Soong; Cheong, Wing Loong; Shaikh, Mohd. Farooq (Frontiers in Neurology, 2022)
Background Post-traumatic epilepsy (PTE) is a devastating neurological outcome of traumatic brain injury (TBI), which may negatively impact the quality of life of patients with TBI, and may impose a huge socioeconomic burden. This burden may be due to long-term functional outcomes associated with PTE, particularly cognitive dysfunction. To date, the relationship between TBI and PTE remains unclear, with little known about how the effect of their link on cognitive function as well. Objective Thus, this systematic review aimed at elucidating the relationship between PTE and cognitive impairment in adults after TBI based on available clinical studies, in hopes to aid in the development of therapeutic strategies for PTE. Methods A systematic literature search was performed using 6 databases; MEDLINE, Embase, CINAHL, Psych INFO, Web of Science, and Cochrane to retrieve relevant clinical studies investigating the link between PTE and cognition in the context of TBI. The Newcastle-Ottawa Scale (NOS) was used to assess the methodological quality of relevant studies. Results A total of six eligible studies were included for critical appraisal in this review after performing the inclusion and exclusion criteria, which involved 1,100 individuals, from 1996 to 2021. The selected studies were derived from the civilian and military population, with a follow-up period that ranged from 6 months to 35 years. The average quality of the involved studies was moderate (6.6, SD = 1.89). Five out of six studies found poorer cognitive performance in people with PTE, compared with those without PTE. Although the association between PTE and cognitive impairment was insignificant after controlling for specific covariates, there was a statistical trend toward significance. Conclusion This systematic review suggests that there may be a possible link between PTE and cognitive decline in TBI patients, with the latter being reported to occur up to 35 years post injury. Variations in sample sizes, follow-up periods, and neuropsychological assessment tools may be the limitations affecting the interpretation and significance of this relationship. Therefore, future studies with standard cognitive assessment tools may be warranted to solidify the link between TBI-PTE-cognitive dysfunction, prior to the development of therapeutic strategies. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020221702, prospero identifier: CRD42020221702.